Video tracker based on an FPGA board with a digital camera - Cheong, Kok Siang. (2009)
In this project, the author has carried out a series of evaluation on two major tracking algorithms which is target representation and localization and filtering and data association. The first method is mainly performing the object tracking using each object’s feature such as color, intensity, and contour while the other method is base on the mathematical equations defined by scientists. By evaluating each method’s pros and cons, the author has decided to perform object tracking by combining certain ideas from both methods.